Financial Development and Environmental Degradation in Indonesia: Evidence from Auto Regressive Distributed Lag Bound Testing Method - Fitriyah, Nur (International Journal of Energy Economics and Policy, 2019)
Financial sector can carry a negative impact on power consumption by advancing energy efficient technologies through technological advancements in the power industry to decline toxic carbon emanations. Therefore, the emphasis of the current investigation is on identifying the empirical connection between financial advancement and carbon emission in the developing country of Indonesia. In addition, given the relevant significance, the study also aims to examine the contribution of energy consumption and economic growth of Indonesia in influencing environmental degradation in the country. The results of ARDL bound testing confirm a valid long-run relationship between financial advancement, energy consumption, economic growth, and carbon dioxide emission in Indonesia. The result further suggested that financial advancement, energy consumption, and economic growth have a positive and significant impact on carbon emission in both the long and short run period. The study recommends that the government needs to divert its energy and also financial institution toward the green investment and environmental friend energy utilization, which ultimately help to reduce the carbon emission level in Indonesia. Keywords: Financial Advancement, Energy Consumption, Auto Regressive Distributed Lag, Indonesia JEL Classifications: G00, Q50 DOI: https://doi.org/10.32479/ijeep.8286